2016
DOI: 10.1097/jsm.0000000000000270
|View full text |Cite
|
Sign up to set email alerts
|

Concussion Management Practice Patterns Among Sports Medicine Physicians

Abstract: Sports medicine physicians seem to have clinical expertise in the management of sport-related concussion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 19 publications
(32 reference statements)
0
28
0
Order By: Relevance
“…175 -177 Acetaminophen and nonsteroidal anti-inflammatory medications were the most commonly used. [175][176][177] Emergency department physicians reported high rates of use of ondansetron. 176 Primary care physicians also report a frequent recommendation of melatonin and amitriptyline.…”
Section: Acute Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…175 -177 Acetaminophen and nonsteroidal anti-inflammatory medications were the most commonly used. [175][176][177] Emergency department physicians reported high rates of use of ondansetron. 176 Primary care physicians also report a frequent recommendation of melatonin and amitriptyline.…”
Section: Acute Managementmentioning
confidence: 99%
“…176 Primary care physicians also report a frequent recommendation of melatonin and amitriptyline. 175,177 The chronic use of acetaminophen or nonsteroidal anti-inflammatory medications is discouraged because they may contribute to medication overuse headaches. 178 There are currently no medications that are specific to treat concussion.…”
Section: Acute Managementmentioning
confidence: 99%
“…Concussion, a mild traumatic brain injury resulting in immediate and transient symptoms, is a common diagnosis seen in the emergency department, as well as primary care and sports medicine offices. Recent studies have shown that visits to emergency rooms for sports‐ and recreation‐related concussion have increased dramatically over the last decade . Earlier studies regarding the epidemiology of concussions have estimated that 300,000–3.8 million concussions occur annually in the United States .…”
Section: Introductionmentioning
confidence: 99%
“…Most of these are nonspecific and may also be seen in other medical conditions; therefore, it is important to relate the onset of signs and symptoms to the head injury (4,11,19,20). Some signs and symptoms may appear soon after the concussion, while other may appear over a period of several days to weeks.…”
Section: Clinical Aspectsmentioning
confidence: 99%
“…Management of young athletes with concussion has evolved rapidly over the past decade resulting the development of different guidelines that describe a fundamentally similar approach for the treatment of concussions (1)(2)(3)(4)(19)(20)(21)(22). Concussion severity grading based on various criteria such as the presence or absence and duration of loss of consciousness, confusion and memory are no longer used or found clinically useful (1,5,10).…”
Section: Managementmentioning
confidence: 99%